Continuous Professional Development with a Problem-Solving Approach for Elementary Madrasah Teachers in Madiun Regency - Mifftahusyai'an, Mohammad; Mulyoto, Galih Puji; Munir, Misbah; Fahruddin, Mohammad Mukhlis; Sanihah, Mutia (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The implementation of the Pancasila Student Profile Strengthening Project (P5) in the Independent Curriculum is a new face of Education in Indonesia. However, in fact, there are still many teachers who experience obstacles in understanding P5 in MI. The purpose of this study is to determine the strategy and impact of continuous professional development in the workshop on making the Pancasila student profile strengthening project module (P5) for MI teachers in Madiun Regency.The research approach used is action research. Action research is known as Participatory Action Research (PAR). The steps used combine problem solving methods. Data collection techniques use documentation, interviews, observations and questionnaires. Data analysis techniques use interactive analysis techniques (interactive analysis model).The results of the study showed that there was an increase in teachers' abilities in designing creative and contextual modules. In addition, they were able to apply the principles of active and collaborative learning. The impact of the workshop on making the Pancasila student profile strengthening project module (P5) for MI teachers in Madiun Regency can be seen from the increase in teachers' understanding and skills in implementing project-based learning that encourages students to think critically, creatively, and provide solutions in facing real-life challenges. The output obtained from this activity is a learning module that is ready to be used by teachers to teach the values of the Pancasila Student Profile in elementary schools, as well as improving the quality of the learning process that is more oriented towards the formation of student character in accordance with the Pancasila Student Profile.